The politics of regional trade in Iraq, Arabia, and the Gulf, 1745-1900 - Fattah, Hala Mundhir 1950- (SUNY series in the social and economic history of the Middle East, 1997)
Examines the development of a socioeconomic region in Iraq, Arabia, and the Gulf during a 150-year period, focusing on regional ties through long-distance trade networks